2019
DOI: 10.4257/oeco.2019.2304.11
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Phenology of Macrophyte Community in Response to Wetland Flooding Cycle

Abstract: The phenology of macrophytes in response to environmental stressing factors is easily evidenced in wetlands under seasonal floods, such as the Pantanal. In these environments, the survival and establishment of seedlings of aquatic plants are restricted, limited to episodes with the presence of water, resulting in posterior sexual propagation for dispersal of seeds adapted to hydrochory, overcoming the dry period dormant in the sediment. We described the reproductive phenology of the macrophyte community in rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The substrate where species occur usually reflects water availability and is especially important for vegetation that is subjected to variations in flooding regimes (Nunes da Cunha and Junk, 2004;Catian et al, 2019). Water availability favors greater allocation of this resource to flowers, allowing growth in size (Teixido et al, 2016;Kuppler and Kotowska, 2021;Roddy et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The substrate where species occur usually reflects water availability and is especially important for vegetation that is subjected to variations in flooding regimes (Nunes da Cunha and Junk, 2004;Catian et al, 2019). Water availability favors greater allocation of this resource to flowers, allowing growth in size (Teixido et al, 2016;Kuppler and Kotowska, 2021;Roddy et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Gallou et al [ 35 ] reported diurnal temperature to be widely correlated with the size of vascular plants. Likewise, precipitation may be related to reproductive aspects of Nymphaeaceae, as it has been reported that there is a correlation between flowering and seasonal flooding cycles in aquatic plants [ 36 ]. Studies have also shown that different fish and snake species exhibit both divergent and convergent patterns of evolution in response to climate change [ 4 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…(1) dry, from July to September, when there is a strong hydric deficit; (2) rising water, from October to December, when the precipitation period begins; (3) high water, from January to March, when flooding is at the highest level; and (4) receding water, from April to June, when the water level begins to decline [69,70].…”
Section: Study Areamentioning
confidence: 99%